1990
DOI: 10.1111/j.1365-2044.1990.tb14454.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful difficult intubation Tracheal tube placement over a gum‐elastic bougie

Abstract: SummaryA randoniised study was carried out to assess the effect of tracheal tube rotation on the passage of a tube over a gum-elastic bougie into the trachea in 100 patients. Key wordsDififficult tracheal intubation; gum-elastic bougie.Successful management of a difficult intubation using a gum-elastic bougie is completed in two phases. The first involves passage of the bougie through the larynx into the trachea. The methods employed to recognise the position of the bougie in the trachea when the vocal cords … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(71 citation statements)
references
References 8 publications
0
68
0
3
Order By: Relevance
“…It is not possible to make a direct comparison of the frequency of impingement between the sexes from our data. Dogra et al [4], also used 8.0-and 9.0-mm tubes for women and men and reported a similar 50% rate of glottic impingement, but did not comment on the influence of gender. It is logical to expect a bigger tube to cause more impingement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not possible to make a direct comparison of the frequency of impingement between the sexes from our data. Dogra et al [4], also used 8.0-and 9.0-mm tubes for women and men and reported a similar 50% rate of glottic impingement, but did not comment on the influence of gender. It is logical to expect a bigger tube to cause more impingement.…”
Section: Discussionmentioning
confidence: 99%
“…This has become the standard manoeuvre to overcome the obstruction when impingement occurs. Dogra et al [4] in their influential study investigated this phenomenon and found that impingement was common and that the 90CCWR manoeuvre was highly effective in overcoming the obstruction. They reported impingement in 12 ⁄ 25 subjects with the tube in the neutral position and in none of 25 subjects with 90CCWR.…”
mentioning
confidence: 99%
“…Intubation with tracheal tube railroaded directly over the fibrescope For this method of fibrescope guided intubation, a 6.0 mm reinforced tracheal tube (Mallincrodt, Hazelwood, MO, USA), with the tube bevel facing posteriorly [14,15], was mounted on the fibrescope by the investigator. Total timing of the first intubation consisted of two timed sections: time 1 -from the participant's picking up the fibrescope to obtaining a view of the carina; and time 2 -from the start of railroading the tube into the trachea over the fibrescope, to removal of the fibrescope and delivery of a single breath.…”
Section: Methodsmentioning
confidence: 99%
“…18,19 This has also been described with the passage of the tube over a gum-elastic bougie. 20 The main cause of this constriction is the creation of a cleft along the tube bevel by the difference in the OD of the fibrescope or bougie and the ID of the tube. In this study, we used a PAEC with an OD of 4 mm and a tracheal tube with ID of 7.5 mm.…”
Section: Discussionmentioning
confidence: 99%